Lectotypification of three names in the genus Henckelia Spreng. (Gesneriaceae) - Janeesha, A.p.; Nampy, Santhosh (Phytotaxa, 2016)
The genus Henckelia Sprengel (1817: 402) was re-established by Weber & Burtt (1997), with approximately 180 species, to include most of the Malesian, Sri Lankan and south Indian species of Didymocarpus Wallich (1819: 378). Weber et al. (2011) and Middleton et al. (2013) based on molecular data redefined the genus and included only 56 species. Subsequently three more species were added to the genus, H. pradeepiana Nampy, Manudev & Weber in Manudev et al. (2012: 119), H. sivagiriensis (Rajakumar et al. 2009: 481) Kumar (2014: 149) and H. bracteata Janeesha & Nampy (2015: 53) while Middleton et al. (2015) transferred H. smitinandii ( Burtt 2001: 89) Middleton & Möller in Weber et al. (2011: 776) to the genus Chayamaritia Middleton & Möller (2015: 1961). At present the genus includes 58 species distributed in Sri Lanka, southern and northeastern India, Nepal, Bhutan, southern China, northern Vietnam, northern Laos and northern Thailand.